2005
DOI: 10.1002/chin.200550212
|View full text |Cite
|
Sign up to set email alerts
|

New CVD Precursors Capable of Depositing Copper Metal under Mixed O2/Ar Atmosphere.

Abstract: New CVD Precursors Capable of Depositing Copper Metal under Mixed O 2 /ArAtmosphere. -The structure of the Cu complexes (VI) (orthorhombic, space group Pna21, Z = 4) and (VII) (monoclinic, P2/n, 2) are determined by single crystal XRD. CVD experiments show that both complexes are capable of depositing high-quality Cu 0 films at temperatures of 275-300°C using an inert argon carrier gas with low O2 concentrations (2-8%). The best copper thin film showed a purity of ≈96 at.% and a resistivity of 2.1 µΩ·cm (bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…That this is not necessarily the case, was found by Lay et al [190], while studying two new self-reducing partially fluorinated Cu(II) bis(iminoalkoxide) and bis(aminoalkoxide) complexes. 2-8% of O 2 mixed into the Ar carrier gas led to the best results for resistivity and deposition kinetics in the range of 275-300 ºC possibly because oxygen aids the oxidation of ligand fragments during the decomposition process and thus reduces film contamination.…”
Section: Deposition Of Metal Complexesmentioning
confidence: 87%
“…That this is not necessarily the case, was found by Lay et al [190], while studying two new self-reducing partially fluorinated Cu(II) bis(iminoalkoxide) and bis(aminoalkoxide) complexes. 2-8% of O 2 mixed into the Ar carrier gas led to the best results for resistivity and deposition kinetics in the range of 275-300 ºC possibly because oxygen aids the oxidation of ligand fragments during the decomposition process and thus reduces film contamination.…”
Section: Deposition Of Metal Complexesmentioning
confidence: 87%
“…40 The bridging alkoxide groups are located in both axial and equatorial positions, while the nitrogen atom of the aminoalkoxide group is in the axial position with the N−In−O bond angle to the opposite, axial alkoxide group being 147. A number of other metal complexes (Ti, 70 Zr, 70 Hf, 70 Ru, 39 Pd, 38 Ir, 215 and Cu 37,43 ) based on fluorinated amino-and imino-alkoxide ligands have also been reported. X-ray diffraction studies revealed a monomeric structure in all cases, with the anticipated coordination according to the type of ligand framework.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Consequently, the TG curves of 3 and 4 appear to exhibit four steps whereas 2 shows five steps of thermal degradation at a glance. Magnitude of final residue from all the three complexes is higher than that calculated for one mole of metal [28,[29][30][31] probably due to carbonaceous matter alongwith reduced metal. Further, it is worth to be mentioned that rerecorded TG curve of the heterobimetallic complex 4 on simultaneous TGA/DTA-MS device is superimposable on its original TG curve (Fig.…”
Section: Thermal Behaviour Of 2 Under Helium Atmospherementioning
confidence: 98%